BIODIVERSITY OF THE GUT MICROBIOTA OF Epilachna vigintioctopunctata USING ILLUMINA MiSEQ PLATFORM (Applied Biological Research, 2024)
The insect gut is a complex system colonized by a consortium of microbes  whichshare a symbiotic relation with the host and also contribute to its growth,  development, immunity and defense against its enemies, reproduction and  speciation, thereby play a crucial role in its survival. Hence understanding the  role of these bacteria is a crucial step for using them in microbial control of  pests. In present study, a 16S microbiome profiling of gut of Epilachna  vigintioctopunctata was carried out. The study revealed 553 operational  taxonomic units (OTUs). The majority of bacterial OTUs belonged to the  phylum Proteobacteria, followed by Bacteroidetes, Firmicutes and  Actinobacteria. The majority of bacterial OTUs belonged to the family  Halomonadaceae which was the most abundant taxa in larval gut. The study  provides a baseline information on gut inhabiting microbes of E. vigintiocto punctata up to the genus level for most phyla.
Keywords: Epilachna vigintioctopunctata; gut bacteria; Halomonadaceae; Illumina MiSeq; Proteobacteria; 16s rRNA gene sequencing